Polyaniline inside the pores of high surface area mesoporous silicon as composite electrode material for supercapacitors. Issue 27 (10th June 2022) - Nawaz, Saima; Khan, Yaqoob; Abdelmohsen, Shaimaa A. M.; Khalid, Sadia; Björk, Emma M.; Rasheed, Muhammad Asim; Siddiq, M.
Abstract : Magnesiothermic reduction was used to reduce mesoporous silica to mesoporous silicon which can host a variety of materials such as polyaniline and has potential to be used in supercapacitors. Abstract : Mesoporous silicon (mSi) obtained by the magnesiothermic reduction of mesoporous silica was used to deposit polyaniline (PANI) in its pores, the composite was tested for its charge storage application for high performance supercapacitor electrodes. The mesoporous silica as confirmed by Small Angle X-ray Scattering (SAXS) has a Brunauer–Emmett–Teller (BET) surface area of 724 m 2 g −1 and mean pore size of 5 nm. After magnesiothermic reduction to mSi, the BET surface area is reduced to 348 m 2 g −1 but the mesoporousity is retained with a mean pore size of 10 nm. The BET surface area of mesoporous silicon is among the highest for porous silicon prepared/reduced from silica. In situ polymerization of PANI inside the pores of mSi was achieved by controlling the polymerization conditions. As a supercapacitor electrode, the mSi–PANI composite exhibits better charge storage performance as compared to pure PANI and mesoporous silica–PANI composite electrodes. Enhanced electrochemical performance of the mSi–PANI composite is attributed to the high surface mesoporous morphology of mSi with a network structure containing abundant mesopores enwrapped by an electrochemically permeable polyaniline matrix.